Direct Stakeholder's Perception of PPA Clauses in the Nepalese Environment - Shrestha , R.B.; Ogunlana, Stephen (Penerbit Universiti Sains Malaysia, 2007)
The paper analyses the perceptions of the stakeholders regarding the key issues in Power Purchase Agreements (PPAs) in the Nepalese Environment. A total of 90 questionnaires representing sponsors, utility, lenders and government officials were used for the study. The questionnaire sought the perception of the stakeholders regarding the significance (importance) of the clauses and the likelihood of inclusion of the clauses in PPAs. Comparison of the ranks of means was conducted by Kruskal-Wallis tests to see the significance of the differences in responses of the stakeholders and Mann-Whitney tests to see the significance of the differences of the pairs of stakeholders. Data analysis showed clauses where the prime stakeholders have similar stands and clauses where the perceptions are divergent. The findings of this paper will help the stakeholders in negotiating PPAs.